The Problem Of The Narrator In Short Stories (Example Of The Stories Of Togay Murad And Khurshid Dostmukhammad) (Texas Journal of Philology, Culture and History, 2026)
In this article, the problem of the narrator in the short story genre is analyzed theoretically and practically. The stories of Togay Murad and Khurshid Dostmukhammad reveal the artistic functions of the narrator, his relationship with the author and the reader, the degree of reliability, and psychological and aesthetic possibilities. As a result of the research, it is determined that the problem of the narrator in the works of both authors has been found in different artistic solutions